MANAJEMEN DONASI LOGISTIK KESEHATAN PADA MASA TANGGAP DARURAT BENCANA GUNUNG MERAPI DI DISASTER RESPONSE UNIT FK UGM - , Hadi Sukanto ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Vulcanic eruption of Merapi in Yogyakarta on October 26, 2010 brought about life toll and infrastructural damage. Disaster mitigation concerns with preparedness that can be realized only through a wellplanned disaster management. The need for health care services increased during the disaster emergency response, beginning with the coming of medical aid from the domestic or foreign donor. Humanity donor frequently causes the problem to the recipient. Therefore, dependable human resources are nevessary to manage the donation. In this case, university is traditionally accepted as the leading sector since it has human resources and community based characteristic. Accordingly, university is believed to give accurate information to the public. Objective: To find out the profile of dination and management of health donation logistic during emergency response periof after Merapi eruption disaster at DERU Faculty of Medicine Gadjah Mada University Method: A qualitative research was conducted using explorative case study design. Subjects of the study are stakeholders that played important role in the management of health logistic donation during the emergency response period after Merapi eruption disaster at DERU Faculty of Medicine Gadjah Mada University. Data were collected through in-depth interview and document study. Results and Discussion: Donation or aids were received and distributyed by DERU Faculty of Medicine Gadjah Mada University. The donation came in the forms of medicine, equipment, volunteer, and cash. Healh logistic donation was managed by DERU Faculty of Medicine Gadjah Mada Univerity by referring to Perka PNPB No. 13/2008. Conclusion: Donation received during emergency response period came in the form of logistics for curative and emergency treatment. Cash money was managed in a proper and transparenty way to be used in the areas that were easy to access and did not suffer from serious infrastructure damage.